PENGARUH PEMBERIAN TERAPI AKUPRESUR TERHADAP POLA MAKAN PADA BALITA BGM DI WILAYAH KERJA PUSKESMAS SEKOTONG - I Made Eka Santosa; Djatiswara Satyadharma; Dina Fithriana; Ni Made Sumartyawati (PrimA: Jurnal Ilmiah Ilmu Kesehatan, 2025)
THE EFFECT OF ACCUPRESSURE THERAPY ON TODDLER’S DIET IN THE PUSKESMAS SEKOTONG ABTRACT The nutrition of toddler is an important must be know an the need for attention. The proportion of malnourished children in western Lombok 8,5% and malnutition reach 19,9%. Therefore KEP for toddler reach 28,4%. The most important can be affect the nutrional state is diet. The mostly of dietary for toddler due to spleen and digestive sytem problems. Yhat efforts for solving problems is non farmacological therapy that acupressure therapy. The study was pre experiment with one group pra-post test design. The population in all BGM toddlers. The sampling method used is purposive sampling. Sample used 28 BGM toddlers.  The instrument used was the dietary questionnaire Analysis using Wilcoxon Signed Rank Test. The result of of study a diet before acupressur therapy was mosttly in the category. After acupressure therapy there is enough categories.  Has the effect of accupressure therapy on toddler’s diet in the puskesmas sekotong. The conclusion less toddler’s diet can be improved by acupressure therapy so that toddlers diet can increase. The suggestion in this reseach can be refrence in improving services, especially toddlers diet with acipressure therapy. Keywords: Acupressure Therapi,  Dietrary Habit, Toddler